2021
DOI: 10.1016/j.ijid.2021.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of Vi-typhoid conjugate vaccine co-administration with routine 9-month vaccination in Burkina Faso: A randomized controlled phase 2 trial

Abstract: In 2017, the World Health Organisation (WHO) pre-qualified a single-dose typhoid conjugate vaccine (TCV) and identified TCV co-administration studies as a research priority. Accordingly, we tested co-administration of Typbar TCV 1 (Bharat Biotech International) with measles-rubella (MR) and yellow fever (YF) vaccines. Methods: We conducted a randomized, double-blind, and controlled, phase 2 trial in Ouagadougou, Burkina Faso. Healthy children aged 9-11 months were randomized 1:1 to receive TCV (Group 1) or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…More recently, Typbar TCV was shown to be immunogenic in Burkinabe infants aged 9–11 months (88%) 28 days after vaccination. 26 A similar TCV, produced by another manufacturer, which is also conjugated to tetanus toxoid and licensed for use in India, showed a 100% seroconversion in Indian children from 6 months to 12 years of age 42 days after vaccination, and an 84% seroconversion rate 12 months after vaccination. 27 In the five aforementioned trials, 14 , 24 , 25 , 26 , 27 TCVs were well tolerated with mild reactogenicity, most commonly fever and pain at injection site.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Typbar TCV was shown to be immunogenic in Burkinabe infants aged 9–11 months (88%) 28 days after vaccination. 26 A similar TCV, produced by another manufacturer, which is also conjugated to tetanus toxoid and licensed for use in India, showed a 100% seroconversion in Indian children from 6 months to 12 years of age 42 days after vaccination, and an 84% seroconversion rate 12 months after vaccination. 27 In the five aforementioned trials, 14 , 24 , 25 , 26 , 27 TCVs were well tolerated with mild reactogenicity, most commonly fever and pain at injection site.…”
Section: Discussionmentioning
confidence: 98%
“…A Phase 3 study of over 28,000 children in Malawi compared TCV against meningococcus A vaccine and found an overall efficacy of 81 percent (444). Two Phase 2 studies in Burkina Faso confirmed the safety of TCV and its compatibility with other routine immunizations (445,446). These results suggest TCV can play a crucial role in mitigating the impact of S. Typhi, including antimicrobial-resistant infections.…”
Section: Development Of Vaccines Against Salmonellamentioning
confidence: 97%
“…Results from Burkina Faso on coadministration of TCV with yellow fever and measles-rubella vaccines at 9 months of age and group A meningococcal conjugate vaccine at 15 months old showed comparable TCV antibody responses in the countries where efficacy has been demonstrated ( Table 2 ), again confirming the consistency in the performance of this vaccine across diverse settings. For all vaccines tested—yellow fever, measles-rubella, and group A meningococcal conjugate—antibody responses were similar in the groups receiving concomitant TCV as compared to the groups not receiving concomitant TCV [ 23 , 24 ]. This demonstrates safe coadministration is possible, which facilitates incorporation into routine immunization schedules.…”
Section: Tyvac Clinical Trialsmentioning
confidence: 99%